PENDAMPINGAN DESA MANDIRI PEDULI GAMBUT DI SUMATERA UTARA - Sudibyo, Mufti; Syarifuddin, Syarifuddin; Prastowo, Puji; Eddiyanto, Eddiyanto; Sihite, Onggal; Syahputra, Ricky Andi; hutahaean, Harvei Desmon; Nasution, Zuhairiah; Nst, Mutiara Agustina (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Peatland Care Independent Village (DMPG) program in North Sumatra, implemented in 2024, was designed to enhance environmental quality, protect, and sustainably manage peatland ecosystems. The program involved structured community engagement through various stages, including the recruitment of community facilitators, technical training, the establishment of peatland ecosystem task forces, the development of community activity plans (RKM), and the implementation and presentation of these plans. It was carried out in 12 villages across four districts in North Sumatra. Activities focused on local economic development, such as crop and livestock farming, handicraft production, and capacity building for the community. The stages of the DMPG program are implemented simultaneously and continuously, involving all levels of society and monitored by the university and a delegation from the Ministry of Environment and Forestry. At the end of the program, an evaluation was conducted to measure the impact on the quality of the peatland environment and the economic improvement of the communities in the 12 target villages. The results showed significant improvements in the environmental quality of peatland areas and local economic growth. A survey conducted across 12 villages revealed that 10 villages considered the program highly beneficial in improving the environmental quality of peatland areas, while 2 villages found it beneficial. Regarding economic benefits, 8 villages reported significant improvements in local economies, and 4 villages reported moderate benefits. The program successfully raised community awareness of the importance of peatland conservation and fostered an effective collaborative model involving universities, government agencies, and local communities. These findings underscore the importance of an integrated approach to restoring the ecological functions of peatlands and improving the welfare of surrounding communities.Program Desa Mandiri Peduli Gambut (DMPG) di Sumatera Utara tahun 2024 dirancang untuk meningkatkan kualitas lingkungan, melindungi, dan mengelola ekosistem gambut secara berkelanjutan. Program ini melibatkan pendampingan masyarakat melalui tahapan yang mencakup rekrutmen fasilitator masyarakat, bimbingan teknis, pembentukan tim kerja ekosistem gambut, penyusunan rencana kegiatan masyarakat (RKM), hingga pelaksanaan dan ekspos RKM. Program ini diterapkan di 12 desa yang tersebar di empat kabupaten di Sumatera Utara. Aktivitas melibatkan pengembangan ekonomi berbasis lokal seperti budidaya tanaman dan ternak, produksi kerajinan, serta peningkatan kapasitas masyarakat. Tahapan program DMPG dilaksanakan secara bersamaan dan berkesinambungan dengan melibatkan seluruh lapisan masyarakat serta mendapat pendampingan dari Universitas Negeri Medan serta di monitoring oleh delegasi Kementerian Lingkungan Hidup dan Kehutanan. Di akhir program, dilakukan evaluasi untuk mengukur dampaknya terhadap kualitas lingkungan lahan gambut serta peningkatan ekonomi masyarakat di 12 desa sasaran. Hasil program menunjukkan peningkatan signifikan dalam kualitas lingkungan sekitar ekosistem gambut serta pertumbuhan ekonomi lokal. Selain itu, program ini berhasil meningkatkan kesadaran masyarakat terhadap pentingnya pelestarian gambut dan menciptakan model kolaborasi yang efektif antara perguruan tinggi, pemerintah, dan masyarakat. Berdasarkan survey yang dilakukan kepada 12 desa, Dari segi peningkatan kualitas lingkungan sekitar lahan gambut, 10 desa menyatakan program DMPG ini sangat bermanfaat dalam meningkatkan kualitas lingkungan sekitar lahan gambut, dan 2 desa menyatakan bermanfaat. Dari segi peningkatan ekonomi masyarakat, 8 desa menyatakan sangat bermanfaat bagi peningkatan ekonomi masyarakat dan 4 desa menyatakan bermanfaat. Program DMPG memiliki manfaat Hal ini menegaskan pentingnya pendekatan terintegrasi untuk memulihkan fungsi ekologis gambut dan meningkatkan kesejahteraan masyarakat sekitar.